KESALAHAN PROFESIONAL DOKTER DAN PUTUSAN HAKIM: DILEMA DALAM PELAYANAN MEDIS - Seran, Marcel (Fakultas Hukum Universitas Muhammadiyah Yogyakarta, 2016)
The relationship between the doctor-patient is a very unique law. The uniqueness of this legal relationship beside based on the law; the element of trust is becoming a cornerstone of the creation of the medical practitioners’ acts of effort on the patient, so that the ethical and moral aspects are involved in it. As a cornerstone of patient-doctor relationship, it is built upon trust; it is not an option of the way the medical dispute resolution between doctor-patient but as a must. But in fact, it is not the case, since it is not uncommon for the court becomes the choice of the medical dispute settlement. There would be a reaction from among the medical profession. They assess that the law interferes too far with the autonomy of the medical profession. To overcome this problem then it is offered medical dispute solutions through the judicial profession; there is a need to involve medical profession as a member of the judges. So there is no longer an accusation that the public court judge does not understand the medical issues. In that way, the medical dispute resolution can be achieved.